Energy Harvesting on Footsteps Using Piezoelectric based on Circuit LCT3588 and Boost up Converter - Iswanto Iswanto; Slamet Suripto; Faaris Mujaahid; Karisma Trinanda Putra; Noor Pratama Apriyanto; Yosi Apriani (Institute of Advanced Engineering and Science, 2018)
Piezoelectric utilization as a generator is an effort to obtain electrical energy that refers to the concept of energy harvesting referring the development of piezoelectric as a generator that converts the pressure or vibration generated from steps into electrical energy that can be used on low-power electronic devices. Because the use of piezoelectric as a generator allows the use in charging low voltage, a larger resource is required in different series. Based on the problem, an energy harvesting device and a voltage amplifier are created to increase the voltage of the pizoelectric output. An arduino microcontroller is used to control the energy harvesting device and voltage booster. It is required approximately 10 steps to charge four AA 1.2 Volt batteries and 80 steps to charge two 12 volt batteries respectively.